Improving students understanding about the value of Place through demonstration method of second Grade students in sd negeri 28 pasar gompong Kecamatan lengayang kabupaten pesisir selatan - Heppilinda Heppilinda (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Education is a way of establishing human ability to use their rational / thoughtfulness as an answer in dealing with various problems that arise in the future. One of the goals of education is to improve the quality of human resources. With good education we will easily follow the development of the times in the future. The research objective of this studywas to determine whether the use of methods of demonstration can improve understanding of place value in the second grade students of SD Negeri 28 Gompong Market Lengayang District of South Coastal District. The purpose of this learning improvement research was to determine whether the use of methods of demonstration can improve understanding of place value in the second grade students of SD Negeri 28 Gompong Market Lengayang District of South Coastal District. This study on peningkata n understanding of the value of using the demonstration carried out through several tahapan.Tahapan in question is planning,observation, and reflection. Results from this study is appears 18 students have been able to understand the material value of the place through the method of demonstration and almost all of the students has increased very significantly from cycle 1 to cycle 2. It is proved that the use of highly precise method of demonstration to enhance students' skills in particular about place value. A significant increase starting from pre cycle (55%), then on cycle 1 increased to 65% and cycle 2 increased to 90%